Empowering Women through Financial Inclusion in Zimbabwe Is the Gender Gap Not Encroaching This Noble Cause? - Lettiah Gumbo; Precious Dube; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
One of the most effective catalysts of economic growth of any nation is obviously financial inclusion. However, in developing countries such as Zimbabwe gender gap is still an impediment to the achievement of financial inclusion for all. Research findings for this paper show that, increasing women’s financial opportunities and financial awareness on how to access financial products and services will go a long way in reducing the gender gap. Furthermore, increasing access to and use of quality financial products and services is essential to inclusive economic growth and poverty reduction. Although the government of Zimbabwe is taking steps to increase women financial inclusiveness, research shows that women in Zimbabwe trail behind men in as far as access to financial services is concerned. Zimbabwean communities remain dominantly patriarchal and women are always lagging behind in developmental projects meant for their empowerment. This paper seeks to assess the implementation of women’s financial inclusion highlighting opportunities and barriers such as the gender gap and how this may be overcome. The study is qualitative in nature and therefore makes use of interviews and questionnaires for data collection. It is envisioned by the researchers that the research findings will be beneficial to women; their empowerment and development and national development. It is hoped to change the way in which the banking and financial sectors deal with women’s financial inclusion for the betterment of their livelihoods. Furthermore, women’s financial empowerment will improve livelihoods of many families given the caring nature of mothers, sisters, aunts and grandmothers.